# Ramesh sit around a round table with some other men. He has one rupee more than his right person and this person in turn has 1 rupee more than the person to his right and so on, Ramesh decided to give 1 rupee to his right & he in turn 2 rupees to his right and 3 rupees to his right & so on. This process went on till a person has 'no money' to give to his right. At this time he has 4 times the money to his right person. How many men are there along with Ramesh and what is the money with poorest fellow.

This question is related to Infosys Interview

Showing Answers 1 - 3 of 3 Answers

#### hbt

• May 10th, 2006

I think the problem is stated wrongly.

say, there are 3 persons and let us assume that

a has 5 rupees

b has 4 rupees

and c has 3 rupees  as given in the problem....

But by the problem c should have 1 rupee  more than that of the person sitting at right. ie c should have a+1 rupee

Which never can happen!!!!!!!!!!

correct me if anyone got a better answer.

#### gaurav4067 Profile Answers by gaurav4067

• Dec 7th, 2010

Here, consider there are n number of persons sitting on the table.
Let Ramesh has Rs. x.
Then the person to his right will have (x-1) then to his right will have (x-2)
and so on till the person to the left of ramesh have Rs (x-(n-1))

Here it is said that x gives Re 1 to his right and he in turns give Rs2 to
his right and the process continuess untill we get a person who cannot give to
his right i.e he is let with no money.

In the 1st round person to the right will be left with Rs x-2, to his right
will have x-3 and so on and the person to the left of Ramesh have Rs (x-n)
And now Ramesh has Rs(x +n-1).

In the 2nd round person to the right will be left with Rs x-3, to his right
will have x-4
and so on and the person to the left of Ramesh have Rs (x-(n+1))
And now ramesh has Rs(x + 2(n-1))

Let this process continues for r rounds
Then
person to the right of Ramesh has (x-r-1)
person to the left of Ramesh has (x-(n+r-1))
and Ramesh has (x + r(n-1))

Now we have a condition that we stop when we have a person who has 0 sum
Here person to the left of Ramesh has Rs.0
i.e x=n+r-1

Also ramesh has 4 times the sum of the person to his right
i.e x+r(n-1) = 4(x-r-1)
i.e 3x -4 = 3r + nr
=> 3(n+r-1) - 4 = 3r + nr
=> 3n = nr +7

Now if the process completes in 1 round then r=1
we get 2n = 7
this can not be the number of persons

Now when r=2
we get n=7
=> x = 8

Thus Ramesh has Rs. 8 and the person to his right will have 7,6,5,4,3,2

Proof:
In the 1st Round
Ramesh's right = 6
Ramesh's left = 1
Ramesh = 14

In the 2nd round
Ramesh's right = 5
Ramesh's left = 0
Ramesh = 20

and 20 = 4(5)

Was this answer useful?  Yes

#### Suraj Grewal

• Feb 11th, 2012

There are 3 persons sitting with the right hand of Ramesh
assume Ramesh=4
a=3
b=2
c=1
Ramesh gives 1 rs/- to a he has 3 left
now a has 4 and gives 2 to b remaining a has 2
now b has 4 and gives 3 to c remaining b has 1
now c has 4 and gives 4 to Ramesh and remaining c has 0.

### Give your answer:

If you think the above answer is not correct, Please select a reason and add your answer below.  